PENGEMBANGAN DESAIN INSTRUKSIONAL PELATIHAN JARAK JAUH ONLINE DI BALAI DIKLAT KEAGAMAAN JAKARTA - Marina Setiawati (JENTRE, 2021)
The purpose of developing instructional is to contribute to the concept of thought in consulting at BDK Jakarta, particularty in developing instructional design to online training. Secondly, is to foster the creativity of Widyaiswara (Instructors), so that they can contribute to online training development. The consulting concept is expected to mediate instructors develop the online training designs in the future. Consultancy is initiated with situation analysis, and data collection stage is taken before designing and planning a consulting program. Situation analysis aims to collect information including types and forms of activities, parties or the public involved, actions and strategies to be taken, tactics, and the budget needed to implement the program. The result shows the consultation as an online training transformed into a new type of instructional design. This new type of instructional design has been validated by experts and peers through discussion.